Bowel obstruction without history of laparotomy: Clinical analysis of 70 patients. Issue 11 (15th August 2016) - Yoshimaru, Koichiro; Kinoshita, Yoshiaki; Matsuura, Toshiharu; Esumi, Genshiro; Wada, Momoko; Takahashi, Yoshiaki; Yanagi, Yusuke; Hayashida, Makoto; Ieiri, Satoshi; Taguchi, Tomoaki
Abstract: Background: Determining the cause of bowel obstruction without a history of laparotomy (BO without HL) is difficult and can result in delay of treatment and development of a potentially life‐threatening situation. We herein investigated the clinical characteristics of pediatric patients who underwent laparotomy due to BO without HL. Methods: All surgical pediatric patients aged <16 age who were diagnosed with BO without HL between January 2004 and September 2014 were included. Etiology of BO, intraoperative findings and postoperative outcome were investigated retrospectively. Results: Seventy patients were diagnosed with BO without HL in this period. In these 70 patients, malrotation ( n = 34), intussusception ( n = 19), internal hernia ( n = 6) and Meckel's diverticulum ( n = 5) were predominantly identified. Regarding preoperative definitive diagnosis, prevalence of internal hernia, Meckel's diverticulum or idiopathic volvulus was significantly lower than that of malrotation or intussusception ( P < 0.05). Intraoperatively, the rates of strangulation and bowel resection were 55.7% and 30.0%, respectively. The optimal time for emergency operation in order to avoid strangulated bowel resection was <19 h from onset of symptoms. Conclusions: Malrotation and intussusception are major causes of BO without HL in children, but internal hernia, Meckel's diverticulum and idiopathic volvulus should always be taken into account, particularly because of the preoperative diagnostic difficulty and resulting high rate of intestinal resection. In order to avoid resection of the bowel, surgery should be done within 19 h before bowel ischemic change occurs.